Virtual stadium tours and museums in football clubs? - Tobar, Felipe Bertazzo (2021)
In the last decade, a few football clubs have become truly global tourist attractions after receiving thousands of visitors interested to take behind-the-scenes venue tours and to explore their museums. For instance, while the Barça Stadium Tour and Museum - the most visited museum in Catalunya - registered an average attendance of two million tourists, per year, and a profit of €58 million in 2019 the Tour to Bernabéu attracted 1.3 millions of visitors in 2018, meaning it was the third most popular museum in the city of Madrid1. In the UK, the dispute for visitors between the two most victorious clubs made both Anfield and Old Trafford top touristic attractions in Liverpool and Manchester, respectively. In 2019, after several years behind its fierce rivals, the Liverpool Stadium Tour and Museum received around 340,000 visitors, a superior number than registered by the historical “The Beatles Story Exhibition”. By its turn, in 2018, when the Manchester United Stadium Tour and Museum became the most popular paid attraction in the city of Manchester, it attracted around 316,000 visitors.